Child labor in Latin America: The reality of child exploitation in the açaí harvest in northern Brazil - Santos, Glenda Lima dos; Batista, Iana Lorena Pinto; Lopes , Júlia de Araújo; Campos, Tatyane de Araújo (Seven Editora, 2023)
This article analyzes child labor in Latin America, aiming at the açaí harvest as a cultural expression of the population of northern Brazil. Acknowledging that climbing the açaí tree is classified as one of the worst forms of child labor, triggers a conflict between cultural representation and prohibited work, for which a solution of intercultural dialogue, programs that include the population and the need for national action to combat child labor are proposed. DOI:https://doi.org/10.56238/interdiinovationscrese-065